2013
DOI: 10.1017/s0007114512006083
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation of young broiler chickens with Capsicum and turmeric oleoresins increases resistance to necrotic enteritis

Abstract: The Clostridium-related poultry disease, necrotic enteritis (NE), causes substantial economic losses on a global scale. In the present study, a mixture of two plant-derived phytonutrients, Capsicum oleoresin and turmeric oleoresin (XT), was evaluated for its effects on local and systemic immune responses using a co-infection model of experimental NE in commercial broilers. Chickens were fed from hatch with a diet supplemented with XT, or with a non-supplemented control diet, and either uninfected or orally cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
72
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(83 citation statements)
references
References 38 publications
4
72
0
5
Order By: Relevance
“…Herbs and spices are potential antimicrobial agents that can be used against various pathogens and as alternative natural antibacterial to replace antibiotic (Lee et al, 2013). According to Abou-Elkhair et al (2014) suplementation of black pepper and coriander seeds or their combinations in feed enhance the performance and health status of broiler chickens.…”
Section: Introductionmentioning
confidence: 99%
“…Herbs and spices are potential antimicrobial agents that can be used against various pathogens and as alternative natural antibacterial to replace antibiotic (Lee et al, 2013). According to Abou-Elkhair et al (2014) suplementation of black pepper and coriander seeds or their combinations in feed enhance the performance and health status of broiler chickens.…”
Section: Introductionmentioning
confidence: 99%
“…Emadi and Kermanshahi (2007) found that serum immunoglobulins of chickens were also affected by the inclusion of turmeric powder into the diets. The chickens fed turmeric-supplemented diet showed enhanced systemic humoral and cellular immunities (Kim et al, 2013;Lee et al, 2013). The balance between reactive oxygen species (ROS) and the cellular antioxidant defenses decides the amount of ROS in the cells (Burton and Jauniaux, 2011) leading to the formation of lipid peroxidation products such as MDA (Droge, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Capsicum oleoresin has been proposed to reduce the incidence of this disease, considering its well-known anti-inflammatory and antibiotic effects in human and veterinary medicine . Capsicum and TRP oleoresins jointly applied to broiler chickens infected with Clostridium perfringens, Eimeria maxima and oocysts has been probed successfully to reduce gut lesion scores, while such combination decreased serum α-toxin levels and several intestinal cytokines levels, among other beneficial effects (Lee et al, 2013).…”
Section: Feeding Trials Using Trp In Conjunction With Other Active Agmentioning
confidence: 99%